Developing Islamic Suggestopedia-Based Classroom Management At Islamic Boarding Schools In Lampung Province (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted at a boarding school in Lampung. The research object consisted of three Islamic boarding schools: Al-Ismailiyun Islamic Boarding School, South Lampung, Darul 'Ulya Kota Metro Islamic Boarding School, and Riyadlatul ‘Ulum Islamic Boarding School,  East Lampung. In general, this research aimed to analyze, validate, and test the effectiveness of class management in Islamic boarding schools in Lampung province. The approach applied in this research was development research using the ADDIE model. This research was a classroom management development research based on Islamic suggestopedia. The results revealed several important findings regarding classroom management in Islamic boarding schools in Lampung province. First is the condition of Class Management which has been applied in Islamic boarding schools. The second is the finding of a form of Islamic Suggestopedia-based Class Management which can increase the learning  effectiveness at Islamic boarding schools in Lampung Province. The third is the result of implementing Islamic Suggestopedia-based Class Management which can increase the learning effectiveness at Islamic boarding schools in Lampung Province.